Analysis of The Impact of Infrastructure on Palm Oil Production in Smallholder Plantations - Susan Novrini; Mhd. Ilham Riyadh; Mhd. Sofyan Harahap (Postgraduate, University of Mataram, 2025)
This study aims to analyze the influence of infrastructure and economic factors including accessibility, construction, electricity availability, land area, and Gross Regional Domestic Product (GRDP) on smallholder palm oil production in Muko-Muko Regency, Bengkulu Province. Using secondary data from 2005 to 2020 obtained from the Central Bureau of Statistics, the research employs multiple linear regression analysis based on the Ordinary Least Squares (OLS) method. The F-test results indicate that the five independent variables collectively have a significant effect on palm oil production (F = 4.00; Sig. 0.029), confirming that the model is statistically valid in explaining production variation. However, partial t-tests reveal that accessibility, construction, electricity, land area, and GRDP do not individually exhibit significant effects. These findings suggest that production performance is not driven by a single factor but rather shaped by the combined interaction of infrastructure conditions and regional economic dynamics. The discussion highlights that inconsistent infrastructure development, declining land area, and limited technological adoption among smallholders contribute to suboptimal production despite rising electrification and economic growth. Overall, the study underscores the importance of integrated infrastructure development, effective land-use planning, and technological support for smallholders to sustainably enhance palm oil productivity and strengthen regional economic resilience.